ERROR ANALYSIS IN USING â€œGOING TOâ€ AND â€œWILLâ€ IN SENTENCES; AT MA NW MISPALAH CENTRAL LOMBOK IN ACADEMIC YEAR 2013/2014 - Terasne, Terasne; Sugianto, Nanang (IKIP Mataram, 2015)
The research entitled ?Error analysis in using ?going to? and? will? in sentences; at Ma NW Mispalah Central Lombok in academic year 2013/2014? is aimed to find out the errors that students make in using going to and will in sentences. The sample of this research is all of the students at MA NW Mispalah Central Lombok that consists of one class with the total 51 students. Collecting the data of the study, the researcher uses grammar test as the main instrument which was distributed to the whole samples. The four steps; identification, classification, description and explanation were used to analyzed the data in this study. The conclusion of the study concluded that the errors that students made are categorized into omissions errors, addition errors and miss-formation errors. Students omitted the ?going to? and ?will?, copulas and auxiliaries which must appear in the well-formed English sentences, they added going to and will and copulas which must not appear in the well-formed English sentences, they miss-formation the going to and will, copulas and auxiliaries by using the wrong forms of morphemes or structures, they also made the incorrect placement of verbs, adverbs and objects or complements of the sentences. The total percentage of miss-formation error categories, the writer found that the most likely committed by the students is miss-formation of going to and will. From 7, 2 % of miss-formation categories, about 2, 9 % are miss-formation of ?going to? and ?will?.